Prevalence of Medications Errors and Factors of Harmful Errors in Neonates and Paediatrics at Tertiary and Paediatric Hospitals: A Multicenter Study (American Journal of Life Science and Innovation, 2024)
Medication errors (ME) are human mistakes that may occur during drug use, prescribing administration or monitoring. This study aimed to determine the Prevalence of MEs among pediatric patients receiving tertiary treatment in pediatric speciality hospitals and describe their patterns and causes. Three institutions participated in a multicenter retrospective analysis. Reports of all MEs involving paediatrics aged ≤13 years who were hospitalised or visited the Emergency Department or outpatient clinics were reviewed 1 January 2019 - 31 December 2019. The National Coordinating Council for Medication Error Reporting and Prevention classification was used to categorise MEs and to define PRME (category CI) and patient–harming MEs (category EI). A retrospective study was conducted with a total of 318 MEs reported, with an overall prevalence of 0.9 per 1,000 patients. The Prevalence was markedly lower in the CHT (0.35 / 1,000 patients) than in KAMC and KFSH&RC (1.73 and 3.5). The highest rate of MEs was observed in admitted wards (14.69 / 1,000 patients). Most commonly, MEs occurred at the prescribing stage (81.1%), were caused by a physician (83.3%), and were discovered by the pharmacist (85.5%). Improper medication dosage (34.0%), frequency (14.2%), and duration (10.4%) were the three most common forms of MEs. Paediatric inpatient treatment has a significant frequency of MEs, accounting for 24% of hospitalisations. The ME may not get to the patient if independent double-check prescriptions, accurate medication reconciliation of new prescriptions against the previously prescribed, and improved medicine labelling and packaging techniques are used.